Meminimalisir Sampah Plastik Melalui Pemanfaatan Botol Bekas Sebagai Akuarium Perikanan di SD Negeri 22 Seladu - Saputri, Dwi; Kusumawardani, Sagita; Febri, Febri; Yayan, Krisentia; Lugeri, Leo; Hanavi, Muhammad Ilham; Agam, Beryaldi; Urabi, Debby; Haq, Izhar Amirul; Jordi, Jordi; Kristiandi, Kiki; Sigiro, Oktavia Nurmawaty; Agusti, Evelin; Mahgfirah, Indria; Audina, Mia; Sangkala, Sangkala; Masara'T, Sudirman (PUSAT PENELITIAN DAN PENGABDIAN PADA MASYARAKAT (PPPM) POLITEKNIK NEGERI SAMBAS, 2025)
Plastic waste is a serious environmental problem that requires immediate handling, especially in educational environments. SD Negeri 22 Seladu faces the challenge of managing plastic waste, especially used bottles, which have not been utilized optimally. This condition shows the need to increase students' awareness of plastic waste management and the provision of environmentally based learning media. This service activity aims to minimize plastic waste, increase students' understanding of waste management, and create learning media in the form of aquariums from used bottles. The method used includes preparation stages, delivery of materials, and practice of making aquariums from used plastic bottles. Activities are carried out with a participatory approach to actively involve students. The results of the activity show that students are able to understand the concept of recycling, increase creativity, and have a higher awareness of the importance of protecting the environment. This program provides significant educational and environmental benefits. By using used bottles as a learning medium, this activity can be used as a model for environmental education in other schools to support sustainable plastic waste management.